2020
DOI: 10.21608/aimj.2020.23054.1113
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sonographically thick placenta and its effect on the fetal and maternal outcome

Abstract: Background:The placenta is responsible for the nutritive, respiratory and excretory functions of the fetus. It is often overlooked in the routine evaluation of the normal gestation, receiving attention only when an abnormality is detected. Aim of the work: To determine the prevalence of sonographically thick placenta and the relation of thick placenta to fetal & maternal outcome. Patients and methods: prospective study included 25 pregnant women with thick placenta, attending to El-Hussein Obstetric outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Eltagy et al [7] decided predominance of sonographically thick placenta, connection of thick placenta to fetal and maternal intricacies during pregnancy and the result of these pregnancies. They presumed that expanded placental thickness isn't analytic of a particular issue however may add to the administration of an embryo in danger.…”
Section: Discussionmentioning
confidence: 99%
“…Eltagy et al [7] decided predominance of sonographically thick placenta, connection of thick placenta to fetal and maternal intricacies during pregnancy and the result of these pregnancies. They presumed that expanded placental thickness isn't analytic of a particular issue however may add to the administration of an embryo in danger.…”
Section: Discussionmentioning
confidence: 99%
“…The study enforced that fetal growth restriction is preceded by reduced placental growth. (29) . They suggested that placental thickness can serve as a measure for determining LBW infants (14,29) .…”
Section: Table-3 Sensitivity Specificity Positive Predictive Value An...mentioning
confidence: 99%
“…(29) . They suggested that placental thickness can serve as a measure for determining LBW infants (14,29) . In the present study, the diagnostic accuracy of placental thickness was measured by ultrasonography in detecting IUGR babies keeping actual birth weight as the gold standard.…”
Section: Table-3 Sensitivity Specificity Positive Predictive Value An...mentioning
confidence: 99%